2022
DOI: 10.54986/irjee/2022/jan_mar/155-159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Entrepreneurship on Women Entrepreneurs

Abstract: The movement of entrepreneurship promotion and development in the past few decades has gone a long way in North East India, particularly in the state of Assam. Moreover, North East is seen as a region where more women are involved in income generating activity than women of the other parts of the country. Women play an important role in the development of our country. Therefore, entrepreneurship development among women is a global issue. It is therefore, important for development of a family and social progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
5
0
0
Order By: Relevance
“…Two factors were included under factor IV with factor loading of 0.697 for subsidies from the government and 0.796 for improving contacts with government officials and named as Government supportive domain. The results showed similar results with Chauhan & Saikia, [15].…”
Section: Resultssupporting
confidence: 87%
“…Two factors were included under factor IV with factor loading of 0.697 for subsidies from the government and 0.796 for improving contacts with government officials and named as Government supportive domain. The results showed similar results with Chauhan & Saikia, [15].…”
Section: Resultssupporting
confidence: 87%
“…56.70% of rural women entrepreneurs have 3-6 members in their family, possibly due to preferences for nuclear families among young and middle-aged individuals. Marriage is prevalent among rural women entrepreneurs, with 95.50% being married and 2.50% widowed, consistent with previous studies (G. Nagamuthu, 2018; Ram et al, 2013; Seemaprakalpa, 2016) [9,12,14] . The majority (60.8%) of rural women entrepreneurs have 3 to 4 children, similar to findings by Sowmya (2009) [16] .…”
Section: Methodssupporting
confidence: 89%
“…The majority of rural women entrepreneurs (84%) are in the age range of 25-44 years, reflecting a trend observed in previous studies. A significant portion (44.20%) of women entrepreneurs have a primary degree, while 28.30% are illiterate, aligning with findings by Nalawade and Ingale (2013) [18] and Manisha Singh (2016) [12] . 56.70% of rural women entrepreneurs have 3-6 members in their family, possibly due to preferences for nuclear families among young and middle-aged individuals.…”
Section: Methodssupporting
confidence: 85%
“…Moreover, urban areas have several networking opportunities that foster and encourage the establishment of Startups. The findings are in line with those of Ram et al (2013) [16] , who reported that majority of the Startups are located in the urban areas.…”
Section: Stages Of Developmentsupporting
confidence: 92%
“…The above trend is likely due to entrepreneurs starting their businesses with their own money as their primary source of funding, but when Startups needed financial institutions' support for scaling up, they felt it was challenging to obtain credit from financial institutions due to the cumbersome process and bankers' preference for collateral security rather than looking at financial viability of the Startup. The findings of non-institutional sources of finance were consistent with those of Abdullah et al (2014) and Ram et al (2013) [16] , who arrived at a finding that the majority of agripreneurs relied on their own financial resources.…”
Section: Financial Sourcessupporting
confidence: 89%